The effectiveness of digital entrepreneurship ecosystem toward enriching income generation: The moderating role of entrepreneurial intention - Adam, Sabrinah; Mohd Fuzi, Nursyazwani; Ramdan, Mohamad Rohieszan; Ismail, Albert Feisal @ Muhd Feisal (SAGE Publications Inc., 2025)
This study attempts to examine the functionality of the digital entrepreneurship ecosystem for low-income household Bottom 40 (B40) students toward enriching income generation and entrepreneurial intention as the moderating role in the relationship. This research applied the quantitative method using an online questionnaire. A total of 500 data were gathered from 5 Universities in Malaysia, followed by Partial Least Squares-Structural Equation Modelling (PLS-SEM) analysis to examine the hypotheses suggested in the research. The results implied that the effectiveness of the digital entrepreneurship ecosystem has a positive effect on the enrichment of income generation among B40 students in a higher education institution. It was also shown from the moderating effect analysis that entrepreneurial intention has an important function as a moderator to strengthen the relationship. The research may assist B40 students in a higher education institution for income generation through digital entrepreneurship.